1998
DOI: 10.1161/01.str.29.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke in Young Women and Two Prothrombotic Mutations: Factor V Leiden and Prothrombin Gene Variant (G20210A)

Abstract: Background and Purpose-Factor V Leiden and a prothrombin gene variant, G20210A, are mutations associated with a thrombotic risk. The aim of our study was to assess whether these mutations increase the risk of stroke in women under 45 years of age. Methods-We conducted a case-control study in western Washington state. Case patients were women aged 18 to 44 years with a first stroke (nϭ106). Control subjects were women without stroke recruited from the same region by use of random-digit telephone dialing (nϭ391)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
2
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(95 citation statements)
references
References 38 publications
6
76
2
11
Order By: Relevance
“…Several studies have reported that FVL mutation is not an important risk factor for ischemic stroke (32)(33)(34)(35)(36). In contrast, the present study demonstrated a higher frequency of homozygous and heterozygous FVL mutations in stroke patients than in controls.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Several studies have reported that FVL mutation is not an important risk factor for ischemic stroke (32)(33)(34)(35)(36). In contrast, the present study demonstrated a higher frequency of homozygous and heterozygous FVL mutations in stroke patients than in controls.…”
Section: Discussioncontrasting
confidence: 86%
“…In contrast, the present study demonstrated a higher frequency of homozygous and heterozygous FVL mutations in stroke patients than in controls. The frequency of this mutation in stroke patients was higher than that reported in previous studies (33)(34)(35)(36)(37)(38)(39). Notably, the frequency of the FVL mutation in healthy individuals was similar to that of the general society.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…FVL mutasyonu, Faktör V geninin 1691'inci nükleotidinde arginin yerine glutamin gelmesi ile oluşan bir nokta mutasyonudur. Türklerde FVL mutasyonu %7,1-10,4 olarak en sık mutasyonlardan birisidir 8 . FVL mutasyonu heterezigot hastalarda tromboz riski sağlıklı bireylere göre 7, homozigotlarda ise 80 kat daha fazla tespit edilmiştir 9 .…”
Section: Introductionunclassified
“…Bir çalışmada Protrombin G20210A mutasyonu heterozigot taşıyıcılığı serebral ven trombozlu hastaların %20'sinde bildirilmiştir. Aynı zamanda, Protrombin G20210A mutasyonu arteriyel tromboz riskini de arttırmaktadır 8 .…”
Section: Introductionunclassified